Teaching some geometric concepts through midrib manipulation - Moron, Ma. Bella M. 1949- (1975)
This study introduces midribs as a medium in concretizing abstract concepts in Geometry. Some lessons and activities in geometry have also been developed using midribs as a manipulative device.
Thesis (M.A.T.)--University of the Philippines, Quezon City
Keywords: Geometry -- Study and teaching (Elementary).